Labour market signalling and unemployment duration: an empirical analysis using employer-employee data - Anders Frederiksen; Rikke Ibsen; Michael Rosholm; Niels Christian Westergård-Nielsen (Institute for the Study of Labor (IZA), 2006)
This paper tests the signalling hypothesis using detailed flow-based employer-employee data from Denmark. The primary focus is to explore how the conditions in the pre-displacement firm affect the duration of unemployment. The empirical analysis is conducted within a competing risk framework, with destinations into reemployment and inactivity, which yields more plausible estimates of the signalling effect. It is established that the positive ability signal of being displaced due to a plant closure is significant but also that the signal of displacement from severe downsizing is important. Issues that have previously been ignored in the empirical analysis of the signalling hypothesis such as local labour market conditions, the sector of employment and the duration of the previous employment match are established to be important determinants for the time spent in unemployment. The heterogeneity of the signalling effect across various employee subgroups in the economy is also explored. These findings emphasize that individuals' reemployment prospects are heavily influenced by the labour market history and in particular by the conditions in the firms in which they were previously employed.
Keywords: J64; J65; J68; 330; unemployment duration; signalling; plant closure